(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2001)
A support group for stutterers, created in order to give information about stuttering, changed into therapy group due to the needs and interests of the subjects. A completely integrate program for the treatment of stuttering was designed, with professionals from the areas of psychological therapy and speech therapy. The subjects had weekly sessions with 90 minutes of duration. On the speech session they emphasize aspects of fluent and not fluent speech as rhythm, speed, order, understanding and self-correction. The psychological sessions were conducted using the reference of behavior therapy, and the procedures intended to reduce the anxiety and the shame in frightful situations and build a more adaptive repertory of behavior. The authors analysed the efficiency of this program, developed in a short period of time and in group, about the subjects severity of stuttering.